2019
DOI: 10.1021/acs.analchem.8b05962
|View full text |Cite
|
Sign up to set email alerts
|

Speeding Up the Line-Scan Raman Imaging of Living Cells by Deep Convolutional Neural Network

Abstract: Raman imaging is a promising technique that allows the spatial distribution of different components in the sample to be obtained using the molecular fingerprint information on individual species. However, the imaging speed is the bottleneck for the current Raman imaging methods to monitor the dynamic process of living cells. In this paper, we developed an artificial intelligence assisted fast Raman imaging method over the already fast line scan Raman imaging method. The reduced imaging time is realized by wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…A high-deep convolutional neural network (DCNN) assisted fast Raman imaging method was introduced to investigate living cells. 129 By widening the slit and laser beam, the sample was scanned with a larger step than the one used in the typical fast-line scan Raman imaging. To improve the situation of reduced image quality due to the shorter imaging time, the spectral-data sets were processed via a DCNN regression approach to transform the low-resolution images into the highresolution ones.…”
Section: Temporal Resolutionmentioning
confidence: 99%
“…A high-deep convolutional neural network (DCNN) assisted fast Raman imaging method was introduced to investigate living cells. 129 By widening the slit and laser beam, the sample was scanned with a larger step than the one used in the typical fast-line scan Raman imaging. To improve the situation of reduced image quality due to the shorter imaging time, the spectral-data sets were processed via a DCNN regression approach to transform the low-resolution images into the highresolution ones.…”
Section: Temporal Resolutionmentioning
confidence: 99%
“…In such cases, fast measurements are needed but they suffer from bad data quality, such as extremely high noise or low spectral/spatial resolution. Deep learning has shown its capability of handling this issue in recent publications . For example, an U‐net was applied to stimulated Raman spectra to reduce noise in the data and hence improve the sensitivity, which helps shorten the spectral acquisition time down to 20 μs without losing sensitivity .…”
Section: Deep Learning For Vibrational Spectroscopymentioning
confidence: 99%
“…For example, an U‐net was applied to stimulated Raman spectra to reduce noise in the data and hence improve the sensitivity, which helps shorten the spectral acquisition time down to 20 μs without losing sensitivity . In another investigation the authors applied a deep convolutional neural network to improve the spatial resolution of the Raman hyperspectral data. In this way, the line‐scan Raman measurement was largely accelerated.…”
Section: Deep Learning For Vibrational Spectroscopymentioning
confidence: 99%
“…10 Recently, He et al reported fast imaging by converting a low-resolution image obtained with a few scans to a higher-resolution image using artificial intelligence, trained with a large volume of imaging data. 11 Other developments in spontaneous Raman imaging include multifocus imaging using two-dimensional array illumination, 12 selective illumination for reduced sampling, 13,14 and wide-field imaging. 15,16 Resonance Raman scattering can be employed to enhance the Raman signal of molecules with a chromophore moiety.…”
Section: Introductionmentioning
confidence: 99%